1999
DOI: 10.1111/j.1469-7793.1999.0449p.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative inotropic effects of NO donors in atrial and ventricular fibres of the frog heart

Abstract: The cardiac effects of the NO donors sodium nitroprusside (SNP), S‐nitroso‐N‐acetyl‐penicillamine (SNAP) and 3‐morpholino‐sydnonimine (SIN‐1) were studied in frog fibres to evaluate the contribution of cyclic GMP‐dependent mechanisms. SNP and SNAP (0·1‐100 μM) reduced the force of contraction in a concentration‐dependent manner in atrial and ventricular fibres. This effect was associated with a reduction in the time to peak (TTP) and the time for half‐relaxation of contraction (T½). SIN‐1 (100 μM) also reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 46 publications
3
40
0
1
Order By: Relevance
“…Many studies have demonstrated the positive effect of low concentrations of the nitric oxide/ superoxide donor SIN-1 and of peroxynitrite on basal myocardial contractility [16][17][18]. We confirmed these results in isolated murine cardiomyocytes, in that 10 μmol/L SIN-1 induced an increase in basal [Ca 2+ ] i transient amplitude and myocyte shortening (Fig.…”
Section: Low Sin-1 (10 μMol/l) and Myocyte Contractilitysupporting
confidence: 87%
See 2 more Smart Citations
“…Many studies have demonstrated the positive effect of low concentrations of the nitric oxide/ superoxide donor SIN-1 and of peroxynitrite on basal myocardial contractility [16][17][18]. We confirmed these results in isolated murine cardiomyocytes, in that 10 μmol/L SIN-1 induced an increase in basal [Ca 2+ ] i transient amplitude and myocyte shortening (Fig.…”
Section: Low Sin-1 (10 μMol/l) and Myocyte Contractilitysupporting
confidence: 87%
“…There are many studies which demonstrate a concentration-dependent biphasic effect of peroxynitrite on basal myocardial contractility, but the majority of these studies did not address these effects on β-adrenergic responsiveness [10][11][12][13][14][15][16][17][18]26,28]. In our study, SIN-1 (source of peroxynitrite) had a biphasic effect on murine cardiomyocyte contractility that was not only dependent on concentration, but also on the contractile state of the cardiomyocyte.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition, investigators also demonstrated that the NO donor-induced contractile enhance ment in frog [33] and rodent [34] cardiomyocytes was mediated through a cGMP-independent mechanism. The exact nature of this response remains to be elucidated.…”
Section: Phosphodiesterases and Cyclic Nucleotide Signalingmentioning
confidence: 99%
“…In the coronary vasculature, cAMP and cGMP promote vasodilation that may indirectly affect cardiac performance [52,53] . In addition, the above-mentioned cGMP-independent positive inotropic effects of NO in cardiomyocytes [33,34] might be achieved through direct S-nitrosylation of the excitation-contraction coupling elements, such as the L-type calcium channels [34,54] and RyR [34,55] (Figure 1). …”
Section: Phosphodiesterases and Cyclic Nucleotide Signalingmentioning
confidence: 99%